2014
DOI: 10.1007/s12012-014-9286-7
|View full text |Cite
|
Sign up to set email alerts
|

Can We Predict Clinical Cardiotoxicity with Cardiac Biomarkers in Patients After Haematopoietic Stem Cell Transplantation?

Abstract: The long-term prognosis of patients after haematopoietic stem cell transplantation (HSCT) has greatly improved. Cardiac complications represent unresolved and potentially life-threatening conditions in these patients. We prospectively examined 37 consecutive patients with a median age of 28 years who underwent allogeneic HSCT. Biomarkers of cardiac injury were measured serially before the conditioning regimen, the first day after HSCT and then 14, 30, 90 and 180 days after HSCT. Echocardiography was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…From the regulatory perspective all MSC-based products are classified as ATMPs. ATMPs reflect a complex and innovative class of biopharmaceuticals, as these products are highly research-driven, characterized by innovative manufacturing processes and high complexity (Flory and Reinhardt 2013;Maslova et al 2015;Roziakova et al 2015). The manufacture of ATMPs requires novel approaches to quality control procedures in comparison to standard stem cell grafts.…”
Section: Discussionmentioning
confidence: 99%
“…From the regulatory perspective all MSC-based products are classified as ATMPs. ATMPs reflect a complex and innovative class of biopharmaceuticals, as these products are highly research-driven, characterized by innovative manufacturing processes and high complexity (Flory and Reinhardt 2013;Maslova et al 2015;Roziakova et al 2015). The manufacture of ATMPs requires novel approaches to quality control procedures in comparison to standard stem cell grafts.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in a multi-variate analysis, an elevation of BNP at baseline significantly raised the odds of subsequent cardiac events [49]. Multiple other small studies have found an association between elevation in BNP or NT pro-BNP and left ventricular dysfunction [50][51][52][53][54]. Not all studies have indicated the clear ability of natriuretic peptides to detect cardiotoxicity during anthracycline-based chemotherapy [55••, 56, 57].…”
Section: Anthracycline Cardiotoxicitymentioning
confidence: 99%
“…Other approaches to mitigate the cardiotoxic impact of anthracyclines employ potentially cardioprotective medications, such as ACE inhibitors and beta blockers. Although promising data have been published recently, convincing evidence from large randomized and prospective trials is still needed 3 There are some limitations of our current analysis. First, this was a retrospective study from a single institution.…”
mentioning
confidence: 93%
“…However, HSCT survivors are at risk of developing long term complications, and mortality rates remain four-to ninefold higher than in the general population 3 .…”
mentioning
confidence: 99%
See 1 more Smart Citation